Prognostic Value of APACHE II and RTS in Predicting ICU Mortality Among Multitrauma Patients: A Single-Center Study from Turkey - Ahmet Düzgün; Maşallah Çakırer; Seher Yanatma (Journal of Clinical Medicine, 2026)
Background/Objectives: Trauma remains a leading global cause of mortality and morbidity, particularly in low- and middle-income countries. Multitrauma patients often require intensive care and exhibit high mortality rates. Prognostic scoring systems such as the Acute Physiology and Chronic Health Evaluation II (APACHE II) and Revised Trauma Score (RTS) are widely used to predict outcomes; however, their performance in middle-income settings like Turkey has not been well established. This study aimed to evaluate the prognostic accuracy of APACHE II and RTS in predicting intensive care unit (ICU) mortality among multitrauma patients. Methods: This retrospective observational study was conducted in the General ICU of Diyarbakır Gazi Yaşargil Training and Research Hospital between January 2022 and December 2024. Adult patients (≥18 years) with multitrauma involving at least two anatomical regions were included. Demographic data, clinical scores (APACHE II, RTS, Sequential Organ Failure Assessment [SOFA], Injury Severity Score [ISS], Trauma and Injury Severity Score [TRISS]), laboratory parameters, complications, and outcomes were recorded. Univariate and multivariate logistic regression analyses identified independent predictors of ICU mortality. Receiver operating characteristic (ROC) analysis assessed the discriminatory ability of prognostic scores. Results: A total of 145 patients were analyzed, with an ICU mortality rate of 13.1%. Non-survivors had significantly higher APACHE II (27 ± 4 vs. 13 ± 6, p < 0.001) and SOFA scores (7 [4–13] vs. 2 [1–6], p < 0.001) and lower RTS (4.2 ± 1.7 vs. 7.2 ± 1.1, p < 0.001). Acute kidney injury, sepsis, septic shock, and mechanical ventilation were more frequent among non-survivors (p < 0.01 for all). In multivariate analysis, APACHE II (odds ratio [OR]= 1.54, 95% confidence interval [CI] 1.16–2.04, p = 0.003) and RTS (OR = 0.36, 95% CI 0.16–0.81, p = 0.013) were independent predictors of ICU mortality. ROC analysis showed excellent prognostic performance for APACHE II (area under the curve [AUC] = 0.959) and RTS (AUC = 0.888). Conclusions: In this retrospective single-center cohort, APACHE II and RTS were independently associated with ICU mortality and demonstrated good discriminatory performance for early risk stratification in critically ill multitrauma patients. The lower mortality observed in our cohort should be interpreted cautiously, as it may also reflect differences in case-mix, injury severity, ICU admission practices, and referral patterns. These findings require external validation in larger multicenter cohorts before broader generalization. Future studies should also validate the identified cut-off values and further investigate the prognostic role of biomarkers such as procalcitonin.